2012
DOI: 10.5755/j01.ee.23.2.1543
|View full text |Cite
|
Sign up to set email alerts
|

Modern Model of Interconnection of Inflation and Unemployment in Latvia

Abstract: Globalisation contributes to stabilisation of monetary policy of countries, achievement of price stability and decrease rates of inflation. There is no clear generally accepted concept for "inflation". A number of experts consider inflation to be a complicated multisided process, which depends not only on economical but also on social and political reasons. One of the main aims of state governments and central banks of the majority of world countries is the decrease of inflation due to its negative effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A number of experts consider inflation to be a complicated multisided process, which depends not only on economical but also on social and political reasons. Theory of inflation considers unanimity of three components thereof: excessiveness of currency circulation; depreciation of money; redistribution of income, property and downfall of net remuneration (Kochetkov, 2012).…”
Section: Macroeconomic Factors Influencing the Loan Portfolio Credit ...mentioning
confidence: 99%
“…A number of experts consider inflation to be a complicated multisided process, which depends not only on economical but also on social and political reasons. Theory of inflation considers unanimity of three components thereof: excessiveness of currency circulation; depreciation of money; redistribution of income, property and downfall of net remuneration (Kochetkov, 2012).…”
Section: Macroeconomic Factors Influencing the Loan Portfolio Credit ...mentioning
confidence: 99%
“…ARDL models are among the popular and frequently used approaches in econometric studies, see, e.g., (Marques et al 2019;Menegaki 2019;Kochetkov 2012;Khan et al 2019;Obradovic et al 2017;Ridzuan et al 2017;Kurecic and Kokotovic 2017).…”
Section: Models and Methodsmentioning
confidence: 99%
“…Figure 7 indicates similarly low levels after 2010 directing the analyzed countries towards fulfilling the convergence criteria. Economic analysis of inflation in Latvia is presented in (Kochetkov 2012).…”
Section: % Risk Of Cross-border Conflictmentioning
confidence: 99%
“…Focusing on Latvia, Kochetkov (2012) examined relationship between inflation rate and unemployment rate by estimating the natural rate of unemployment in the country. He concluded that there was a negative association between unemployment and inflation between 1999 and 2008.…”
Section: Literature Reviewmentioning
confidence: 99%